RAPID: characterizing the response of a burned landscape to an unusual and extreme rain event: rainfall data - Nelson, Peter A.; Brogan, Daniel J. (Colorado State University. Libraries, 2015)
This data package was produced by researchers working within the Civil and Environmental Engineering department. The data include real-time kinematic global positioning system (RTK-GPS) survey data of 19 cross-sections and their corresponding longitudinal profiles, photographs, and rain gauge precipitation data collected in two study watersheds (Skin Gulch and Hill Gulch) before and after the September 2013 storms and floods that affected the Colorado Front Range. Pebble counts were also collected in the vicinity of each cross-section.

Precipitation was collected using a tipping bucket rain gauge set to log for each tip. Data is presented in two formats. The NCAR* files are presented in 5-minute totals while the rest of the precipitation is presented at the time of each tip. The precipitation timestamp is in mountain daylight time (MDT).
Rainfall data: RAPID: characterizing the response of a burned landscape to an unusual and extreme rain event
Zip file includes: rainfall measurement csv files and rain gage location csv file.
Skin Gulch and Hill Gulch watersheds are located within the 2012 High Park Fire just west of Fort Collins, Colorado (High Park Fire overview).
Department of Civil and Environmental Engineering
RAPID: Characterizing the Response of a Burned Landscape to an Unusual and Extreme Rain Event
Keywords: topography; erosion; geomorphology; flood; precipitation; survey; wildfire